2020
DOI: 10.1590/0103-8478cr20190506
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of soil organic matter and clay contents by near-infrared spectroscopy - NIRS

Abstract: Among the soil constituents, special attention is given to soil organic matter (SOM) and clay contents, since, among other aspects, they are key factors to nutrient retention and soil aggregates formation, which directly affect the crop production potential. The methods commonly used for the quantification of these constituents have some disadvantages, such as the use of chemical reactants and waste generation. An alternative to these methods is the near-infrared spectroscopy (NIRS) technique. The aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Hence, the increased R 2 in the prediction model, when adding Mehlich‐3 extractable Na and Cu, and pH to EstCEC, might be related to cations occupying variable charges associated with clay particles. The clay prediction models' accuracy using EstCEC and Mehlich‐3 extractable nutrients (Figure 1; Table 2) produced similar results as previous research that used different prediction methods (Chang et al., 2001; Lazzaretti et al., 2020; Pinheiro et al., 2017; Pirie et al., 2005; Terra et al., 2015), indicating the potential use of routine soil analysis data to predict soil clay content.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…Hence, the increased R 2 in the prediction model, when adding Mehlich‐3 extractable Na and Cu, and pH to EstCEC, might be related to cations occupying variable charges associated with clay particles. The clay prediction models' accuracy using EstCEC and Mehlich‐3 extractable nutrients (Figure 1; Table 2) produced similar results as previous research that used different prediction methods (Chang et al., 2001; Lazzaretti et al., 2020; Pinheiro et al., 2017; Pirie et al., 2005; Terra et al., 2015), indicating the potential use of routine soil analysis data to predict soil clay content.…”
Section: Resultssupporting
confidence: 80%
“…The moderate goodness-of-fit statistics (Figure 4) highlight the complexity of SOM and suggest that soils with similar physical-chemical characteristics and management could improve the prediction accuracy. Lazzaretti et al (2020) reported that soil clay content affects the predictive ability of a model to estimate SOM content by NIRS, suggesting that separating soils into groups with similar characteristics can enhance SOM prediction accuracy. Unlike NIRS, where soil mineralogy and particle size can affect the spectra and the predictions (Dalmolin et al, 2005;Lazzaretti et al, 2020;Sousa et al, 2008), SOM prediction based on routine soil-test information might be more influenced by crop management practices and fertilization.…”
Section: Soil Organic Matter Prediction and Validationmentioning
confidence: 99%
See 3 more Smart Citations